Enhanced photosynthetic performance and growth as a consequence of decreasing mitochondrial malate dehydrogenase activity in transgenic tomato plants. - Nunes-Nesi, A; Carrari, F; Lytovchenko, A; Smith, A; Loureiro, M; Ratcliffe, R; Sweetlove, L; Fernie, A (2005)
Transgenic tomato (Solanum lycopersicum) plants expressing a fragment of the mitochondrial malate dehydrogenase gene in the antisense orientation and exhibiting reduced activity of this isoform of malate dehydrogenase show enhanced photosynthetic activity and aerial growth under atmospheric conditions (360 ppm CO2). In comparison to wild-type plants, carbon dioxide assimilation rates and total plant dry matter were up to 11% and 19% enhanced in the transgenics, when assessed on a whole-plant basis. Accumulation of carbohydrates and redox-related compounds such as ascorbate was also markedly elevated in the transgenics. Also increased in the transgenic plants was the capacity to use L-galactono-lactone, the terminal precursor of ascorbate biosynthesis, as a respiratory substrate. Experiments in which ascorbate was fed to isolated leaf discs also resulted in increased rates of photosynthesis providing strong indication for an ascorbate-mediated link between the energy-generating processes of respiration and photosynthesis. This report thus shows that the repression of this mitochondrially localized enzyme improves both carbon assimilation and aerial growth in a crop species.